Biosorption of Antimony Species by Red Macroalgae (Nori) and Cyanobacteria (Spirulina) - Vanessa Egéa dos Anjos; Renata Martins da Silva; Adriano Gonçalves Viana (Orbital: The Electronic Journal of Chemistry, 2025)
A biotechnological study with the Porphyra tenera (red macroalgae, “Nori”) and Spirulina platensis (cyanobacteria) was performed to evaluate the feasibility of non-living biomass as biosorbent for inorganic antimony species to be used in the remediation technology or as solid phase for analytical purposes such as preconcentration. The biosorption of Sb(III) and Sb(V) was studied using batch technique under similar conditions of the aquatic environments. High values of biosorption (over 70%) of both Sb species were determined and factors such as dosage of the biomass, contact time and pH, practically did not influenced in the sorption. The desorption was evaluated using different concentrations of HCl and HNO3. The biosorbents were characterized by X-ray diffraction, scanning electron microscopy (SEM), infrared spectroscopy (FTIR), surface area (BET) and zeta potential. The FTIR analysis after biosorption of the Sb species suggested the involvement of protonated functional groups as amino, carboxyl, and hydroxyl in the interaction mechanism. Thus, both biosorbents are suitable biosorption of Sb from aqueous solution.